Apakah Surplus Pendanaan Memberikan Dampak Terhadap Deviden Yang Dibagikan Pada Perusahaan Terindeks LQ45? - Rino Tam Cahyadi (Akademi Akuntansi YKPN Yogyakarta, 2023)
The LQ45 index is a group of 45 companies that have the largest level of liquidity and market share on the Indonesia Stock Exchange. The facts show that there are still inconsistencies in the distribution of dividends by several LQ45 indexed companies. Researchers investigated the topic of funding surplus factor which means that the company has more cash balances so that it is suspected could influence on the dividends. The novelty of this research is the added intervening variable namely investment opportunity set to prove the indirect relationship between surplus funding and dividends. This study uses intervening variable regression with path analysis testing: Sobel Test in testing the intervening variable. The results showed that the funding surplus proved to have no direct nor indirect effect on dividends. In addition, the researcher also finds that there is no difference in dividends distributed between companies with surplus financial condition and companies with funding deficit.